1993
DOI: 10.1159/000100662
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Thalamotomy and Pallidotomy in Patients with Movement Disorders: Preliminary Results

Abstract: The Leksell Gamma Knife is a useful and safe method to perform thalamotomy and pallidotomy in selected older patients with Parkinson''s disease and related movement disorders. In this preliminary report, 2 of 3 patients with severe intention tremor were relieved of their symptoms by thalamotomy, as were 4 of 7 patients with Parkinson''s tremor. Four of 8 patients had significant improvement of contralateral rigidity following pallidotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 2 publications
0
32
0
Order By: Relevance
“…The effect of the surgery on parkinsonian symptoms is delayed for several weeks to months as the GK-induced lesion develops. There have been few reports [5][6][7][8][9][10][11][12][13][14][15] of short-or longterm complications of GK surgery for PD ( Table 1). This article follows the recent and important review by Lang 4 suggesting that there is little reliable evidence that GK radiosurgery can be safely applied to patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the surgery on parkinsonian symptoms is delayed for several weeks to months as the GK-induced lesion develops. There have been few reports [5][6][7][8][9][10][11][12][13][14][15] of short-or longterm complications of GK surgery for PD ( Table 1). This article follows the recent and important review by Lang 4 suggesting that there is little reliable evidence that GK radiosurgery can be safely applied to patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…1). The authors of several studies have reported success rates in tremor control in patients with PD, essential tremor, and tremor related to multiple sclerosis or other causes 13,17,41,42,43,51,68,69,72 that are comparable to those achieved using other methods. Complications are usually rare, mild, and temporary, although unusual complications 62 and severe, permanent complications 47 have also been reported.…”
Section: Treatment Of Tremorsmentioning
confidence: 92%
“…The first reports of using GKS in the treatment of tremor were published in the early 1990s, when Rand et al 51 in the United States, Lindquist and colleagues 35 in Europe, and Ohye et al 44 in Japan described their experiences. The positive findings of these groups have since been duplicated at numerous treatment centers around the world.…”
Section: Treatment Of Tremorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Included in this review are seven patients described by us in a previous communication. [21] The goals of our study were: 1) to determine the efficacy of the procedure; 2) to see if there is a dose-response relationship; 3) to review the radiological findings of radiosurgical lesioning; and 4) to assess the risks of complications.…”
mentioning
confidence: 99%